Competence to capability: An integrated career framework for sonographers. Issue 4 (November 2019) - Mitchell, P.; Nightingale, J.; Reeves, P.
Abstract: Introduction: Within the United Kingdom sonographers, with ultrasound as their core role, currently have a primary registration as a radiographer or another health professional. Entering with masters level qualifications, and often exhibiting a higher career banding, the sonographer career structure does not align comfortably with the existing health professional frameworks. This study aimed to explore the attitudes and opinions of a sample of practicing sonographers concerning a potential graduate sonographer role and the development of a clinical competence framework required to provide a skills escalator. Methods: A qualitative study using an interpretative framework was undertaken using semi-structured interviews. A homogeneous sample population of ten participants was selected using theoretical purposive sampling. The interview transcripts were thematically analyzed and coded. Results: The themes of implementing change and clinical frameworks were identified along with a sub-theme of clinical competence boundaries. All participants found it challenging to identify a role or clinical competences that a band 5/graduate sonographer could undertake, though more suggestions were offered for a band 6 sonographer. Conclusion: Whilst, within the literature, clinical competences were agreed to provide the cornerstone for defining clinical roles there was some dispute as to the appropriateness of the use of core clinical competences for defining the scope of practice of health professionals above entry level to the profession. The data collected in this study demonstrated that there were skills development between graduate, specialist, advanced and consultant practitioners. Participants were focussed on clinical skills rather than wider capability skills. It is recommended that in order for advanced practice sonographers to map to the new ACP framework less focus on competence and a greater consideration of capabilities is required.